2013
DOI: 10.1039/c3cc40665b
|View full text |Cite
|
Sign up to set email alerts
|

Hollow mesoporous ceria nanoreactors with enhanced activity and stability for catalytic application

Abstract: Novel hollow mesoporous @M/CeO(2) (M = Au, Pd, and Au-Pd) nanospheres are created. The nanospheres can be used as effective nanoreactors with superior catalytic activity and stability for reduction of 4-nitrophenol due to their hollow mesoporous structural features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(83 citation statements)
references
References 25 publications
0
83
0
Order By: Relevance
“…The observed TOF's were comparatively better than those of other catalysts reported in literature [35][36][37][38]. Mn substituted cobalt ferrites as catalysts have the added advantage of their chemical stability, magnetic separability and facile synthetic procedure as compared to other expensive metal catalysts with tedious synthetic procedures.…”
Section: Kinetics Of Reductionmentioning
confidence: 75%
“…The observed TOF's were comparatively better than those of other catalysts reported in literature [35][36][37][38]. Mn substituted cobalt ferrites as catalysts have the added advantage of their chemical stability, magnetic separability and facile synthetic procedure as compared to other expensive metal catalysts with tedious synthetic procedures.…”
Section: Kinetics Of Reductionmentioning
confidence: 75%
“…56 the Pd-1 catalyst demonstrates obviously superior catalytic activity. It is clear that the Pd-1 catalyst prepared in this work is much more active than CNT/PiHP/Pd (300 h -1 of TOF).…”
Section: Resultsmentioning
confidence: 98%
“…Our group has also focused on a Au-CeO 2 hybrid system. 98 We observed that a one-pot self-assembly synthesis could be induced by the addition of HAuCl 4 , Ce(NO 3 ) 3 , L-lysine, polyvinylpyrrolidone and butylmine in water at 80°C for 1 h. Figure 15 shows the corresponding TEM images of the as-obtained Au-CeO 2 hybrids with graphene-like nanostructures. Many drapes were observed in the final products, which could be attributed to the self-folding behavior of the 2D nanostructure.…”
Section: Ceo 2 -Encapsulated Au and Ag Nanostructuresmentioning
confidence: 97%